VD_FINDINFO Arrêt / 2016 / 2 vom 30. März 2016 - VD Tribunal cantonal (2016)
RENTE D'INVALIDITÉ, RÉVISIONPRESTATION D'ASSURANCE, SIMULATION | 28 al. 2 LAI, 4 al. 1 LAI, 17 al. 1 LPGA, 43 al. 1 LPGA, 88bis al. 2 RAI